Unequal childboods: Class, race, and femily life - Lareau, Annette (Berkeley University of California Press, 2011)
Class does make a difference in the lives and futures of American children. Drawing on in-depth observations of black and white middle-class, working-class, and poor families, Unequal Childhoods explores this fact, offering a picture of childhood today. Here are the frenetic families managing their children's hectic schedules of "leisure" activities; and here are families with plenty of time but little economic security.